Analisis Pemahaman Konsep pada Materi Perubahan Wujud Zat di Murid Kelas IV SDN 45 Ampenan - Hidayatun Nisa; Rini Istiana Oktarani; Lisa Sofia Nanda; Lalu Aldi Satriawan; Jundu Muhammad Mufakkirul Islami (STKIP AL HIKMAH SURABAYA, 2026)
Natural Sciences (IPA) contains many abstract concepts that are difficult for elementary school students to understand, including changes in the form of substances. Although closely related to daily life, this topic often leads to misconceptions because the processes cannot be observed directly. Initial observations at SDN 45 Ampenan showed that most fourth-grade students had difficulty answering descriptive questions, classifying changes in the form of substances, and providing accurate examples. This study aimed to analyze fourth-grade students’ conceptual understanding of changes in the form of substances and identify factors contributing to their low understanding. A descriptive quantitative approach was employed with 28 fourth-grade students at SDN 45 Ampenan. Data were collected through descriptive tests, classroom teacher interviews, and learning observations, then analyzed using three indicators of conceptual understanding: restating concepts, classifying objects, and providing examples and non-examples. The findings showed that students’ conceptual understanding remained low. Only 10,7% of students could correctly restate concepts, 21.4% could accurately classify objects, and 32% could provide complete examples. The low achievement was influenced by limited concrete learning experiences, difficulty distinguishing the original substance from the resulting change, and a tendency to memorize object functions rather than understand the process. The study recommends hands-on experiential learning and concrete demonstrations to improve students’ conceptual understanding.